Pelatihan bahasa inggris profesional untuk meningkatkan kemampuan komunikasi karyawan hotel - Lilis Lamsehat Panjaitan; Althaf Gauhar Auliawan; Revasha Oktavia; Friska Anastasya (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
This community service program aims to improve hotel employees’ professional English communication skills through a communicative approach emphasizing speaking and listening competencies. The training was conducted through workshops, role-playing activities, guest service simulations, and the use of digital technology combined with project-based learning methods. This program is expected to enhance employees’ confidence and readiness in interacting with international guests. The program outputs include improved communication skills and the development of a sustainable communication-based training module for hotel management. The results of this program were also documented in an academic publication to support sustainability and the development of similar programs in the hospitality sector.